Levels of Mental Resistance of Young Mothers from Urban Poor Families in The Face of Economic Difficulties - Anne Hafina (Universitas Pendidikan Indonesia (UPI), 2023)
The purpose of this study was to understand the levels of mental resistance of young mothers from urban poor families in the face of economic difficulties. In general, due to protracted economic difficulties, many events make this nation concerned. There are incidents of parents selling their babies, husbands who forcefully sell their wives, and there are also incidents of killing children because they cannot fulfill their needs. In these incidents, it is of course women and children who are the victims. Then, several questions arise: (i) what is the mental resilience of young mothers in facing the current economic difficulties? (ii) Are gender relations between husband and wife in the household not running normally? (iii) This is where research is important so that we can measure the mental strength of housewives in the face of today's difficult life.